The Role of Strategic Agility in Promoting Digital Transformation: A Field Study of Yemeni Banks in the Capital Municipality of Sana’a - Shujaa Aldeen, Mohammed Ahmed; Al-Hemyari, Omaimah Mohammed (University of Science and Technology Journal for Management and Human Sciences, 2024)
The study aimed to examine the role of strategic agility in promoting digital transformation at Yemeni banks in the Capital Municipality of Sana’a. It employed the quantitative descriptive approach and used the questionnaire to collect data from a sample of 385 from a total population of 1901 employees with supervisory posts working for the Yemeni banks in the Capital Municipality of Sana’a. A number of 338 questionnaires were retrieved with a response rate of 88.02%, and all of them were valid for statistical analysis using SPSS v 28. The study revealed that strategic agility across its three dimensions (strategic sensitivity, resource fluidity, and collective commitment) has a significant and positive role in promoting digital transformation in the Yemeni banks, with ’collective commitment’ emerging as the most influential dimension, followed by ’strategic sensitivity’, then ’resource fluidity’. The study concluded that banks that are sensitive to strategic changes, have flexible resource allocation, and prioritize collective commitment are more likely to achieve successful digital transformations. It recommends Yemeni banks focus on strengthening the organizational aspect within digital transformation efforts, work on improving resource fluidity, prioritize strategic sensitivity and alignment, and focus on fostering a collaborative environment where all stakeholders are aligned towards the common goal of digitalization.